2021
DOI: 10.4103/0972-9062.313958
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of Crimean-Congo hemorrhagic fever virus in livestock, Kohgiluyeh and Boyer-Ahmad, Iran, 2017

Abstract: Background & objectives: Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne viral zoonosis with up to 50% mortality rate in humans. In addition to the role of animals in the transmission of the virus and spread of infected ticks through livestock trade, they can be employed as sentinel hosts for monitoring the infection. Iran is one of the endemic counties for CCHF and the disease has been documented in all provinces. However, in some provinces such as Kohgiluyeh and Boyer-Ahmad, the rate of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a study, four sheep (three from Gachsaran and one from Dena regions) reported positive for CCHFV IgG, indicating virus circulation in Kohgiluyeh and Boyer-Ahmad Province, Iran. This finding suggests comprehensive monitoring programs to understand the CCHFV’s circulation in ticks and host animals ( Ghasemian et al, 2021 ). In 1998, 19 confirmed CCHF cases were reported in northeastern Afghanistan, making them the country’s first documented cases.…”
Section: Crimean-congo Hemorrhagic Fever Virusmentioning
confidence: 94%
“…In a study, four sheep (three from Gachsaran and one from Dena regions) reported positive for CCHFV IgG, indicating virus circulation in Kohgiluyeh and Boyer-Ahmad Province, Iran. This finding suggests comprehensive monitoring programs to understand the CCHFV’s circulation in ticks and host animals ( Ghasemian et al, 2021 ). In 1998, 19 confirmed CCHF cases were reported in northeastern Afghanistan, making them the country’s first documented cases.…”
Section: Crimean-congo Hemorrhagic Fever Virusmentioning
confidence: 94%